2008
DOI: 10.1158/0008-5472.can-07-2924
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Levels of Inflammatory Cytokines and Risk of Colorectal Adenomas

Abstract: The association between obesity and colorectal neoplasia may be mediated by inflammation. Circulating levels of C-reactive protein (CRP), interleukin-6 (IL-6), and tumor necrosis factor-A (TNF-A) are elevated in the obese. Adipose tissue can produce and release the inflammatory cytokines that are potentially procarcinogenic. We examined circulating levels of CRP, IL-6, and TNF-A in relation to risk factors and the prevalence of colorectal adenomas. Plasma levels of CRP, IL-6, and TNF-A were quantified in 873 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
202
7
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 254 publications
(221 citation statements)
references
References 43 publications
10
202
7
2
Order By: Relevance
“…Our findings for colorectal adenoma agree with the results of a cross-sectional study in which Kim and colleagues (16) found a positive association with the highest tertiles of IL-6 compared with the lowest tertiles. In that study, however, the levels of IL-6 were below the detection limit (<0.104 pg/mL) in about 50% of the individuals with colorectal adenoma and 65% of the controls, and thus no clear difference in the IL-6 level was demonstrable between the groups.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our findings for colorectal adenoma agree with the results of a cross-sectional study in which Kim and colleagues (16) found a positive association with the highest tertiles of IL-6 compared with the lowest tertiles. In that study, however, the levels of IL-6 were below the detection limit (<0.104 pg/mL) in about 50% of the individuals with colorectal adenoma and 65% of the controls, and thus no clear difference in the IL-6 level was demonstrable between the groups.…”
Section: Discussionsupporting
confidence: 92%
“…To our knowledge, only two previous studies have investigated the relationship between the circulating level of IL-6 and the risk of colorectal adenoma (16,17). Our findings for colorectal adenoma agree with the results of a cross-sectional study in which Kim and colleagues (16) found a positive association with the highest tertiles of IL-6 compared with the lowest tertiles.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Furthermore, IL-6 possesses critical protumorigenic functions thereby increasing the risk for the development of colorectal tumors (7). These findings are consistent with the here-described decrease in tumor incidence in NFATc2-deficient mice when subjected to DSS/AOM model.…”
Section: Discussionsupporting
confidence: 90%
“…The transition from an adenoma to a CRC may take many years and can inevitably result in a series of changes that include altered cytokine secretion and immune cell function in the tumor microenvironment (3)(4)(5). Since the cytokines play an essential role in the communication between tumor cell initiation/progression and host anti-tumor immunity (6)(7)(8)(9)(10)(11), it is important to investigate the cytokine changes in the tumor microenvironment, in order to better understand the transitional mechanisms and design novel interventional strategies. Indeed, in previous studies, we and others have revealed that the colorectal neoplastic transformation leads to a remarkable alteration of cytokine secretion in the tumor immune microenvironment (6,8,12,13), this may have a significant role in predicting the progression from the adenomas to CRCs (12,14,15) and prognosis of the CRCs (7,9,10,12,13,16).…”
Section: Introductionmentioning
confidence: 99%